Transformation Processes in the Healthcare System of Uzbekistan (1917-1991) - Gavkhar Muminova (International Journal on Orange Technologies, 2021)
The article concludes that the global environmental degradation, global warming, and climate change require great attention to the healthcare sector. Despite the fact that in recent years serious reforms have been undertaken in Uzbekistan in the field of healthcare, numerous measures have been taken to develop specialized medical care, protect mothers and children, and provide the population with medicines, there are still many problems that need to be addressed. On the territory of Uzbekistan in the Soviet period, measures were first taken to form a centralized health care system. This process proceeded in a very difficult historical situation, when political, social and economic problems worsened in the country.